Software Implementation of a Secure Firmware Update Solution in an IOT Context - Lukas Kvarda; Pavel Hnyk; Lukas Vojtech; Zdenek Lokaj; Marek Neruda; Tomas Zitta (Advances in Electrical and Electronic Engineering, 2016)
The present paper is concerned with the secure delivery of firmware updates to Internet of Things (IoT) devices. Additionally, it deals with the design of a safe and secure bootloader for a UHF RFID reader. A software implementation of a secure firmware update solution is performed. The results show there is space to integrate even more security features into existing devices.